Effectiveness of Snowball Throwing Model with Word Square Media on Activity and Student Learning Results in Adictive and Psychotropic Materials - Fitri, Nur Khikmah; Irsadi, Andin; Pukan, Krispinus Kedati (Journal of Biology Education, 2017)
The result of observation during the teaching internship program (PPL) show that the teaching and learning activitiesin SMP Mataram Semarang still apply teacher centered learning. Besides, the question and answer session in theteaching and learning activities are still relatively low. Report of the national examination results at SMP MataramSemarang in the academic year 2014/2015 by BSNP indicate that the absorption of students on the material ofaddictive substances and psychotropic is still low at 34,29%. An effort to do is to apply the learning model SnowballThrowing through Word Square media. This study aims to investigate the effectiveness of the learning modelSnowball throring through Word Square media toward the activity and the result of studentâs learning in the materialof addictive substance and psycothropic. This research is a Quasi Experimental Nonequivalent Control Group Design.The results of the study showed that the liveliness of experimental group was 92%, while in the control group was 76%.The classical completeness of cognitive achievement in the experimental group was 88%, while in the control group was48%. The results of t-test showed that there is significant difference on cognitive achievement of the experimental groupagainst the control group. The result of N-gain also showed that the improvement in cognitive achievement of theexperimental group was higher than the control group. The classical completeness of affective achievement of theexperimental group was 92%, while the control group was 80%. It can be concluded that the learning model SnowballThrowing through Word Square media is effective toward the activity and the results of studentâs learning in thematerial of addictive substance and psychotropic. So, Snowball Throwing through Word Square media can bepractice on the material of addictive substance and psychotropic and other material that have same problem.